2010
DOI: 10.1007/s11912-010-0085-4
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Polymorphisms: Role in Response and Toxicity of Tyrosine Kinase Inhibitors

Abstract: Angiogenesis is central to the growth of normal tissues and tumors. Inhibiting this pathway has been a strategy for drug development for tumors not responsive to most agents used in chemotherapy. Notably, signaling mediated by vascular endothelial growth factor (VEGF) is a key target because aberrant signaling via this pathway is frequently associated with neoangiogenesis in tumors. The drug-discovery effort to blunt VEGF signaling has led to the approval of bevacizumab and several receptor tyrosine kinase inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…29 Therefore, we propose that VEGFR-2 genetic polymorphisms may cause structural changes in the receptor and lead to aberrant activation of multiple pathways, including its interaction with P2Y(2)R, with an overall influence on platelet aggregation, which is correlated with CR. [30][31][32] Patients carrying the TT genotype of VEGFR-2 +1192C.T (rs2305948) polymorphism exhibited significantly higher MACE, whereas the GG genotype of …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Therefore, we propose that VEGFR-2 genetic polymorphisms may cause structural changes in the receptor and lead to aberrant activation of multiple pathways, including its interaction with P2Y(2)R, with an overall influence on platelet aggregation, which is correlated with CR. [30][31][32] Patients carrying the TT genotype of VEGFR-2 +1192C.T (rs2305948) polymorphism exhibited significantly higher MACE, whereas the GG genotype of …”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism may be that VEGFR-2 rs2305948 polymorphism, resulting in an amino acid change at the 297th codon, alters VEGFR-2-specific intracellular signaling, resulting in increased incidence of MACE. 30,33,34 VEGF and VEGFR-2 may enhance the pathophysiologic mechanism of plaque formation and plaque destabilization and suggested to be precise triggers for inflammation and neovascularization in atherosclerosis. 35,36 The 2271G.A polymorphism of the VEGFR-2 gene is a functional polymorphism related to the regulation of gene transcription.…”
Section: Vegfr-2 Snp and Clopidogrel Resistancementioning
confidence: 99%
“…Attention has been drawn to the possible role of VEGF-A, HIF1 or VEGFR polymorphisms in influencing the response of tumor cells, mainly to antibody-based therapies [70,71], but also to tyrosine kinase inhibitors [72], or in modulating the risk of treatment-related complications [73]. This possibility has been explored, with controversial results, in various cancer types, including colon [74] and breast cancers [75], but not NETs.…”
Section: Anti-angiogenic Treatments In Netsmentioning
confidence: 99%
“…This idea is supported by recent genetic studies on colon cancers that revealed those patients with reduced COX expression and/or polymorphisms in both COX and PGDH genes may not benefit from NSAID treatment [155-157]. Likewise, screening the same patients for polymorphisms in components of the VEGF-C/VEGF-D signalling pathway may assist in the type of anti-lymphangiogenic therapy administered to improve patient outcome [158, 159]. The interaction of the VEGF-C/VEGF-D and PG signalling axes may provide additional biomarkers such as circulating levels of VEGF-C, VEGF-D and PG for predicting which patients respond to anti-metastatic therapies and/or assessing response during treatment.…”
Section: Introductionmentioning
confidence: 97%